Thirteen scholars reply to Reviel Netz's 'The Place of Archimedes in World History'. (2nd October 2022) - Chemla, Karine
ABSTRACT: This introduction to the issue of Interdisciplinary Science Reviews outlines the rules of the game on which all contributors agreed. Thirteen scholars have responded to a root essay written by Reviel Netz, under the title 'The Place of Archimedes in World History.' The introduction outlines the main lines of the arguments they put forward.